ANALYSIS OF THE HEROISM OF THE FEMALE CHARACTER IN J.S KHAIREN'S NOVEL MELANGKAH - Kinanti Arti Nazihah (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2023)
The novel Melangkah by J.S. Khairen tells the story of the adventures of four Economics students who vacation in Sumba, East Nusa Tenggara, only to get the order of human lives in their hands. The novel will be reviewed using a literary sociology approach. This study aims to describe and explain the author's worldview, the social and cultural background of the community, and the heroic values contained in the novel Melangkah. This research is library research. This study used qualitative methodology. The problem in this study is how the elements of the structure of the novel build literary works and the heroic value of female characters are contained in the novel Melangkah. The study consists of three stages, the first of which is data collection. The technique used is the technique of reading notes. After data collection, the next stage is data analysis. Information is analyzed descriptively. The results of the data analysis are then presented in the form of word exposure through the explanation of the novel Melangkah. The validation used is theory triangulation with stages of reading, recording, and analyzing documents. The conclusion of this research is that the female character in the novel Melangkah reflects all heroic values and their characteristics, namely: courage, confidence, truth-keeping, willingness to endure hardship, and generosity. Patience: Resistant to trials, steadfast, calm, unhurried, and not impetuous. Sacrifice; unyielding and desperate, willing to sacrifice for the benefit of the nation, and a reformer.